2021
DOI: 10.1093/scan/nsab064
|View full text |Cite
|
Sign up to set email alerts
|

Effortless retaliation: the neural dynamics of interpersonal intentions in the Chicken Game using brain–computer interface

Abstract: The desire for retaliation is a common response across a majority of human societies. However, the neural mechanisms underlying aggression and retaliation remain unclear. Previous studies on social intentions are confounded by low-level response related brain activity. Using an EEG-based brain-computer interface (BCI) combined with the Chicken Game, our study examined the neural dynamics of aggression and retaliation after controlling for nonessential response related neural signals. Our results show that aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Moreover, the fact that no differences between the groups were found was not in line with our expectations, since earlier studies did find attenuated P3 and LPP amplitudes in affective picture viewing to be related to antisocial personality and delinquency [ 75 , 88 , 89 ]. Additionally, although studies have found associations between diminished alpha ERD and antisociality [ 69 , 70 ], other studies have found no results concerning alpha ERD (and mu suppression more specifically) and antisocial characteristics [ 75 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the fact that no differences between the groups were found was not in line with our expectations, since earlier studies did find attenuated P3 and LPP amplitudes in affective picture viewing to be related to antisocial personality and delinquency [ 75 , 88 , 89 ]. Additionally, although studies have found associations between diminished alpha ERD and antisociality [ 69 , 70 ], other studies have found no results concerning alpha ERD (and mu suppression more specifically) and antisocial characteristics [ 75 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to aggression, previous studies using resting-state EEG found decreased alpha power in centro-parietal regions to be related to psychopathic personality in violent offenders [69]. A more recent study showed that alpha ERD at frontal sites was related to aggression and retaliation [70], providing support for the idea that aggression results from a decrease in self-control, including dysfunctional emotion regulation.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, we created two tasks measuring different aspects of cooperation and competition to study the role of similarity in dominance, Machivellianism, and hypercompetitiveness in social interactions of siblings. Social interactions are defined as a set of social actions that are dynamically changing, with people able to adjust their choices based on the previous decision of their playing partner 51 . The new tasks necessarily involved: (a) two subjects engaged in the situation, (b) real-time interactions, (c) dynamic changes over time and (d) higher ecological validity compared to standard paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we created two tasks measuring different aspects of cooperation and competition to study the role of similarity in dominance, Machivellianism, and hypercompetitiveness in social interactions of siblings. Social interactions are defined as a set of social actions that are dynamically changing, with people able to adjust their choices based on the previous decision of their playing partner 56 . The new tasks necessarily involved: a) two subjects engaged in the situation, b) real-time interactions, c) dynamic changes, and d) high ecological validity.…”
Section: Introductionmentioning
confidence: 99%